Performance Indicators to Assess Impact of Joint forest Management (JFM) - Sahay, R. R.; Thakre, V. B. (Indian Forester, 2002)
This paper takes a look at the performance indicators by which mainly social, economic and environmental impacts experienced during the implementation of JFM can be assessed in proper perspective. These indicators also help in examining the changing needs and responses of the local communities where participative forestry programmes is under operation.